Targeting the Vasculature of Colorectal Carcinoma with a Fused Protein of (RGD)3-tTF - Zheng-jie Huang; Yilin Zhao; Wei-yuan Luo; Jun You; Shui-wen Li; Wen-cheng Yi; Sheng-yu Wang; Jiang-hua Yan; Qi Luo (The Scientific World Journal)
Purpose. Truncated tissue factor (tTF) fusion protein targeting tumor vasculature can induce tumor vascular thrombosis and necrosis. Here, we generated (RGD)3-tTF in which three arginine-glycine-aspartic (RGD) targeting integrin αvβ3 and tTF induce blood coagulation in tumor vessels. Methods. The bioactivities of (RGD)3-tTF including coagulation activity, FX activation, and binding with integrin αvβ3 were performed. The fluorescent labeled (RGD)3-tTF was intravenously injected into tumor-bearing mice and traced in vivo. The tumor growth, volume, blood vessel thrombosis, tumor necrosis, and survival time of mice treated with (RGD)3-tTF were evaluated. Results. The clotting time and FX activation of (RGD)3-tTF were similar to that of TF (P>0.05) but different with that of RGD (P<0.05). (RGD)3-tTF presented a higher binding with αvβ3 than that of RGD and TF at the concentration of 0.2 μmol/L (P<0.05). (RGD)3-tTF could specifically assemble in tumor and be effective in reducing tumor growth by selectively inducing tumor blood vessels thrombosis and tumor necrosis which were absent in mice treated with RGD or TF. The survival time of mice treated with (RGD)3-tTF was higher than that of mice treated with TF or RGD (P<0.05). Conclusion. (RGD)3-tTF may be a promising strategy for the treatment of colorectal cancer.